2021
DOI: 10.1038/s41598-021-91908-7
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of surgical morbidity of primary versus patch repaired congenital diaphragmatic hernia patients

Abstract: Large studies comparing the surgical outcome of primary versus patch repair in congenital diaphragmatic hernia (CDH) patients are rare. This study aims to evaluate the incidence of surgical complications in both types of CDH repair. PubMed, EMBASE, Cochrane and Web of Science were searched for peer-reviewed articles. Studies on CDH between 1991 and August 2020 were systematically screened and meta-analyses were performed. Primary outcomes of this review were: haemorrhage, chylothorax, recurrences and small bow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…A higher recurrence rate after patch implantation in OS of more than 40% has been observed by several authors (26,33,51,52). In a review on morbidity after CDH repair, the risk of recurrence was reported to be 3.6 times higher after open patch repair (53). Only Riehle reported a low recurrence rate of 4% in 28 patients with an oversize patch in a retrospective study with no structured follow-up (25).…”
Section: Patient Characteristics and Treatment Of Cdhmentioning
confidence: 92%
“…A higher recurrence rate after patch implantation in OS of more than 40% has been observed by several authors (26,33,51,52). In a review on morbidity after CDH repair, the risk of recurrence was reported to be 3.6 times higher after open patch repair (53). Only Riehle reported a low recurrence rate of 4% in 28 patients with an oversize patch in a retrospective study with no structured follow-up (25).…”
Section: Patient Characteristics and Treatment Of Cdhmentioning
confidence: 92%
“…Despite this, the use of patches for repair has been increasing in the last decade. Patients who require a diaphragmatic patch repair are reported to have a risk 2.83 times higher of developing a recurrence ( 26 ). The inability of the synthetic patch to grow with the patient is the mechanism underlying this strong association ( 2 ).…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…The inability of the synthetic patch to grow with the patient is the mechanism underlying this strong association ( 2 ). But, again, the disease's severity and the defect's size may present an underlying independent role ( 26 ). The goal of the patch is to allow closure of the defect without tension on the surrounding structures, despite a large defect size, granting a tension-free suture.…”
Section: Predisposing Factorsmentioning
confidence: 99%
See 2 more Smart Citations